Analisis Perbandingan Query Response Time MariaDB Pada Sistem Operasi Kali Linux dan Ubuntu - Fatimah, Aisyah; Afifah, Nurul; Septiani Kusuma Ningrum (JSI: Jurnal Sistem Informasi (E-Journal), 2025)
Data is a vital resource for organizations that demand unparalleled access speeds and adequate levels of security. Critical components in the data need to be managed effectively and efficiently to enable timely decision-making. This study proposed a comparative analysis of query execution time using MariaDB Database Management System (DBMS) on Kali Linux and Ubuntu operating systems. Researchers identified response times for select, update, and delete operations on variations in data size. This experiment was carried out three times to ensure the consistency of the results. As a result, Ubuntu exhibits a more stable pattern of increasing response time, although it is slower than Kali Linux. Ubuntu performs better in terms of scalability, especially when handling large datasets. Based on this study, the selection of an operating system for database management not only be based solely on query execution speed, but also consider other important factors, such as the operating system's security level, ease of use, and user preferences.